THE GENDER APPROACH AS A MODERN THEORY OF MASCULINITY AND FATHERHOOD - Laura H. Urusova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Recently, in the center of psycho-pedagogical sciences is the study of gender, namely the problem of fatherhood and masculinity. Research interest is dictated by the "shift" of stereotypical gender norms in modern society. Modern parenting roles in the family suffers significant changes. The purpose of this article is to study the phenomenon of fatherhood in the context of traditional and new approaches to the understanding of masculinity as a normative standard. Paternity is understood as a social institution, a system of rights, duties, social stereotypes and requirements to the man as a parent, and rooted in the culture of the regulatory system and the family structure. Another meaning of "fatherhood" - is the practical activities related to the education of children. Paternal identification - a process of self-awareness as a parent and acceptance (or denial) of existing cultural norms of behavior of his father. In accordance with the two models of male behavior (traditional masculinity and the new masculinity) identified and described constructs paternal behavior, "traditional", "absence", "responsible", "new". Gender approach allows us to describe the contents of normative masculinity canon.